2013
DOI: 10.1002/aic.14221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and thermodynamic basis for EGCG‐Keratin interaction‐part II: Experimental investigation

Abstract: In Part I, we reported all-atom, fully solvated molecular dynamics (MD) simulations of epigallocatechin-3-gallate (EGCG) binding to keratin. Herein, we report the second part of experimental investigation on EGCG binding to keratin using ultrafiltration and isothermal titration calorimetry (ITC). The thermodynamic equilibrium of EGCG binding to keratin has been quantitatively determined using ultrafiltration and high-performance liquid chromatography-UV/vis. The relationship confirms multilayer binding of EGCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…() demonstrated that the formation of α‐lactalbumin and epigalocatechin‐3‐gallate (ECGC) complex results in typical exothermic enthalpy change (20 m m phosphate buffer, pH 7.2). Such phenomenon was also observed upon binding of ECGC to lipase (Wu et al ., ), BSA, β‐casein and porcine gelatin (Bohin et al ., ), ovalbumin (Ognjenovic et al ., ), insulin (Wang et al ., ), keratin (Zhao et al ., ), catalase (Pal et al ., ) and Ara h 2 and Ara h 6 proteins (Vesic et al ., ). In the case of Ara h 2 and Ara h 6 proteins, the formation of complex was accompanied by exothermic enthalpy changes (20 m m sodium phosphate, pH 7.2).…”
Section: Thermodynamic Methodsmentioning
confidence: 99%
“…() demonstrated that the formation of α‐lactalbumin and epigalocatechin‐3‐gallate (ECGC) complex results in typical exothermic enthalpy change (20 m m phosphate buffer, pH 7.2). Such phenomenon was also observed upon binding of ECGC to lipase (Wu et al ., ), BSA, β‐casein and porcine gelatin (Bohin et al ., ), ovalbumin (Ognjenovic et al ., ), insulin (Wang et al ., ), keratin (Zhao et al ., ), catalase (Pal et al ., ) and Ara h 2 and Ara h 6 proteins (Vesic et al ., ). In the case of Ara h 2 and Ara h 6 proteins, the formation of complex was accompanied by exothermic enthalpy changes (20 m m sodium phosphate, pH 7.2).…”
Section: Thermodynamic Methodsmentioning
confidence: 99%
“…bond formation), providing accurate, rapid and label free thermodynamic data to determine the changes in enthalpy ΔH, entropy ΔS, and Gibbs free energy ΔG of the adsorption process, as well as provide information on the affinity binding constant K d and the interaction reaction stoichiometry in a single titration experiment. 34 This advanced technology has been widely applied in the chemical and biochemical fields to study protein interactions 35,36 and macromolecular assembly, 37 protein membrane interactions, 38 enzyme kinetics, 39 molecular dynamics simulations, 40 and incremental and DNA-ligand binding. 41 Karlsen et al (2010) conducted a very general study to investigate the use of ITC to determine the thermodynamics of Al 3+ , Cr 3+ , and Pb 2+ binding to the biopolymer chitin, and found that the binding reactions were entropically driven.…”
Section: -14mentioning
confidence: 99%
“…This number of papers is impractical to cite in full so the author has selected approximately 200 that he feels best represents the field and apologizes for any resulting omissions. These references have been classified into the following broad categories: references cited in the introduction, review and perspective articles, methods papers, protein : protein interactions, protein interactions with other ligands, lipids, micelles and membranes, polysaccharides, nucleic acids, synthetic chemicals, polymers and nanoparticles,…”
Section: Introduction To Research Between 2011 and 2015mentioning
confidence: 99%